INSTITUTIONALISATION OF HALAL POLICY: A Case Study in Thailand - Aulia, Vira; Surwandono, Surwandono (Journal of Contemporary Islam and Muslim Societies, 2024)
Abstract: This article aims to analyze how has the halal industry evolved and grown in non-Muslim countries, with a specific focus on Thailand as a case study. This study uses a qualitative research method whose unit of analysis is the Thai government with the object of research being Thailand’s policy in promoting itself as a country that is friendly to Muslim tourists as an effort of public diplomacy. According to the findings, the halal industry, which involves producing and distributing goods and services permissible under Islamic law, is regulated in Muslim-majority countries and is growing in non-Muslim countries. Thailand, a non-Muslim country, has successfully developed its halal industry and is now one of the largest exporters. To overcome barriers, Thailand can promote awareness, encourage community involvement, and improve product quality and diversification. Economically, it can provide financial incentives and support for certification, while ensuring a halal-compliant supply chain. Politically, it can strengthen diplomatic relations and develop consistent halal standards. Addressing political and social unrest can create a stable environment for the halal industry.Keywords: Halal industry, non-Muslim countries, Thailand.